2007
DOI: 10.1080/14786430701216269
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of cube texture in Ni by the addition of W or Mo

Abstract: The development of cube texture after heavy cold rolling ($95%) and annealing has been studied in pure Ni, Ni-5 at% W and Ni-5 at% Mo alloys. The two Ni alloys develop a much sharper cube texture compared to pure Ni, thus indicating the beneficial effect of W or Mo addition. W and Mo enhance the cube texture intensity in Ni by decreasing the volume fraction of the rotated cube grains. The impact of W and Mo addition is seen from a very early stage of recrystallization, where rotated cube grains form in pure Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Earlier studies on the development of deformation and recrystallization textures on pure Ni and Ni-5at.%Mo alloy by the present authors [23] have shown that the presence of Mo in solid solution in Ni enhances the formation of cube texture although the deformation texture of the two materials do not reveal any perceptible difference, qualitatively as well as quantitatively. The difference in the recrystallization textures of the two materials is attributed to the presence of a strong RD rotated cube component in pure Ni as compared to the binary Ni-Mo alloy.…”
Section: B Development Of Texture and Mechanical Properties Of The Mmentioning
confidence: 54%
“…Earlier studies on the development of deformation and recrystallization textures on pure Ni and Ni-5at.%Mo alloy by the present authors [23] have shown that the presence of Mo in solid solution in Ni enhances the formation of cube texture although the deformation texture of the two materials do not reveal any perceptible difference, qualitatively as well as quantitatively. The difference in the recrystallization textures of the two materials is attributed to the presence of a strong RD rotated cube component in pure Ni as compared to the binary Ni-Mo alloy.…”
Section: B Development Of Texture and Mechanical Properties Of The Mmentioning
confidence: 54%
“…Meanwhile, aiming to Ni5W substrate, they have carried out a great deal of studies and obtained excellent results with sharp cube texture. [ 18,19 ] However, insufficient research exists on microstructural transformation during recrystallization and the optimal final annealing treatment for Ni8W/Ni12W/Ni8W. Hence, the aim of this study is to enrich the microstructural transformation during recrystallization treatment and select the appropriate annealing treatment for Ni8W/Ni12W/Ni8W.…”
Section: Introductionmentioning
confidence: 99%